Blurring Boundaries or Why Do We Refer to Sexual Misconduct With Patients as "Boundary Violation". Issue 2 (3rd March 2016) - Cooper, Steven H.
Abstract : I argue for the notion that we reserve the term boundary for the psychic realm because the psychic boundaries of psychoanalysis are so fundamentally complex, dense, and intrinsically confusing that bringing in the realm of behavioral ethical violations is actually unnecessarily vague and mystifying. The notion of a psychological boundary as a term in psychoanalytic work is a fragile, metaphoric construction that allows us to explore fantasy, affect, symbols, and elements of shared and unique realities. Psychoanalysis hinges on a social compact by patients and analysts to open up otherwise forbidden territory offered through this metaphoric construction. Rather than conflate forensic vocabulary ("violation") with a central psychic concept for conducting psychoanalytic work ("boundary"), I suggest that we refer to ethical misconduct in more straightforward conventional terms such as misconduct (behavioral referents) or with specific psychological understandings of the many determinants of this behavior that we have available to us as psychoanalysts.